Analisis Peran Artificial Intelligence (AI) dalam Mengoptimalkan Keuangan Islam - Dwika Mayasari; Mustofa Mustofa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research aims to optimize Islamic finance by utilizing artificial intelligence (AI). This research method uses a descriptive qualitative method. The research data was collected using the literature review method. This study concludes that the challenges faced in the application of Artificial Intelligence (AI) in Islamic finance include Compliance with Sharia Principles, Education and Public Acceptance, Regulatory Complexity, Ethical Issues and Trust, Availability of Qualified Talent. Meanwhile, the application of artificial intelligence (AI) is a solution to various challenges faced by the financial sector including increasing operational efficiency, developing sharia-compliant financial products, improving customer service quality, facing regulatory challenges, and encouraging innovation in Islamic finance. So the application of Artificial Intelligence (AI) in Islamic finance offers various potentials to improve operational efficiency, service quality, fulfillment of sharia principles, and encourage product innovation. However, to maximize this potential, it is important for Islamic financial institutions to continue to innovate, invest in technology, and human resource training to be able to compete in today's digital era.